Designing Mail Server Using Exchange Server At SMPN 17 Bengkulu City - Amelia Purnama Sari; Indra Kanedi; Hari Aspriyono (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
Mail server is one of the most widely used server functions in a school or other company. This is because the email function itself can reduce the cost of correspondence using paper, is faster and more efficient than manual communication and uses attachments that are useful as complements and additional documents related to the contents of the email. Mail Server implementation is done offline by installing on a server that has been prepared. There are 2 operating systems that will be used in the implementation of this mail server, namely for the server (Windows Server 2012) and for the client (Windows 10). The mail server uses Exchange Server 2010 installed on the server (Windors Server 2012). In its application using wireless router with 1 laptop will be used as a server and 2 client laptops, so that the results of the shipment that will be sent to the recipient are automatically stored on the server. While the client accesses the message reception and sends the message. Based on the tests that have been done, if you enter the appropriate username and password, you can enter mail so you can send messages or receive messages from the server to the client and the system is able to send or reply emails from one account to another.